Functional Grammar in the ESL Classroom - Jones, R. author. aut Link
VII, 146 p.
Keywords: A set of easy to use techniques helps students discover for themselves how grammar works in real world contexts and how grammatical choices are not just about form but about meaning. Sample teaching ideas, covering a wide range of grammatical topics including verb tense, voice, reference and the organization of texts, accompanies each procedure.